The Language Factor and the Peace Agenda: A Reaffirmation - Gilbert, Ikechi (International Journal of Arts, Languages, Linguistics and Literary Studies, 2022)
Since interaction between humans takes place through communication and language is the major channel for communication, it can easily be said that language is indispensable in human development. Yet one of the negative recurrent elements in human interaction is the tendency to have disagreements mostly triggered by the wrong use of language. Conflicts are essential components of social life. They can be observed in family tussles, domestic emotional spats, communal disagreements, inter-tribal differences, etc. When a dispute arises, often the best course of action is negotiation to resolve the disagreement. Conflict resolution is a way for two or more parties to find a peaceful solution to a disagreement among them. This article explores the role of language in shaping the way our conflicts unfold and are resolved. It examines the functions of language in conflict and how the different communicative acts relate to speakers’ motivational goals and conflict outcome. It considers different forms of cue response sequences and their role in managing information exchange and structuring relationships in conflicts. It also examines how episodes of language might escalate a conflict or move it towards a resolution. It then explores the link between speech management, thought, and verbal expression, showing that basic language choices have a profound effect on the other party’s perception and the cooperation that ensues. It finally explains how to better use language to resolve or avoid conflicts.